Nuttybub and Nittersing - Gibbs, May, 1877-1969. (Sydney : Angus & Robertson, 1937)
When Nittersing is stolen and taken to live with the bad Banksia Men, Nuttybub and his friend Mr Lizard undertake a series of adventures in order to resuce him.
For children.
Muir, M. A bibliography of Australian children's books
Keywords: Fairies -- Juvenile fiction; Animals -- Juvenile fiction; Australia -- Juvenile fiction